2011
DOI: 10.3171/2011.5.jns102003
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery and shaving: what's the evidence?

Abstract: M ost patients undergoing neurosurgical proce dures dread the commonly performed preopera tive hair removal. Nevertheless, many neuro surgeons insist on removing the patient's hair before sur gery. They claim that this routine prevents postoperative infections and decreases the risk of overlooking wounds or lacerations after head trauma. Moreover, they argue that preoperative hair removal facilitates accurate plan ning of the incision, attachment and/or removal of the drapes, and closure of the wound.However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 24 publications
(111 reference statements)
1
25
1
1
Order By: Relevance
“…), but there is no consensus on this issue in many countries (Broekman et al . , Tanner et al . , Winston , Sebastian , Mitsukawa et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), but there is no consensus on this issue in many countries (Broekman et al . , Tanner et al . , Winston , Sebastian , Mitsukawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, well‐designed and randomised‐controlled studies are needed to verify the effects of regional or strip hair removal on the development of SSI and on the body image of patients (Broekman et al . , Tanner et al . , Winston ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies have demonstrated that shaving in neurosurgery can result in higher infection rates [22,23,24]. Skin injuries occur during shaving and these areas may allow easier bacterial colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…Wrong preoperative protocols comprise inappropriate patient preparation for the surgical procedure (failure to inform the patient of the possible complications, failure to discontinue especial analgesics prior to surgery, such as aspirin and other non-steroidal anti-inflammatory drugs), improper patient positioning to protect the sensitive organs like the eyes, peripheral nerves, and testicles in male patients, and failure to take the necessary measures for full dependence of the abdomen to reduce epidural veins engorgement. Nowadays, there is no hard evidence to support routine preoperative hair removal in spine surgery [414243]. …”
Section: Beware Of Wrong Protocolmentioning
confidence: 99%